D6.10 Report on visiting experts Seminars and trainings (update 1) - Antoniou, Theofilos (My University, 2025)
Deliverable D6.10: Report on visiting experts Seminars and trainings (update 1) focuses on the implementation of technical short courses aimed at keeping ERATOSTHENES CoE researchers and administration staff up to date with state-of-the-art equipment, new software, models, EO data assimilation techniques, advanced algorithms, and machine learning theory and practice. Throughout RP4 (M49–M66), several expert-led talks and training sessions have been implemented to enhance knowledge exchange and professional development. Additionally, this report outlines the implemented talks by invited experts, seminars, workshops, summer school activities and trainings during RP4 and presents the plan for knowledge-transfer and training activities in RP5 (M67–M84), ensuring the continuous upskilling of ERATOSTHENES CoE researchers and strengthening collaborations with leading experts and institutions.
Keywords: Remote Sensing; EXCELSIOR; ERATOSTHENES Centre of Excellence; Earth Observation; capacity building